2013
DOI: 10.1071/rd12196
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the P2X7 receptor in ovarian surface epithelium during the oestrous cycle in the mouse

Abstract: Purinergic signalling has been proposed as an intraovarian regulatory mechanism. Of the receptors responsible for purinergic transmission, the P2X7 receptor is an ATP-gated cationic channel that displays a broad spectrum of cellular functions ranging from apoptosis to cell proliferation and tumourigenesis. In the present study, we investigated the functional expression of P2X7 receptors in ovarian surface epithelium (OSE). P2X7 protein was detected in the OSE layer of the mouse, both in situ and in primary cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…The functional role of P2X7 was investigated in situ by TUNEL assay. P2X7 stimulation with BzATP induced apoptosis in OSE cells and was differential throughout the oestrous cycle; DNA fragmentation was greater during proestrous [70]. These findings contribute to the idea that local factors, such as ATP, may participate in a proposed cyclic proliferation-death equilibrium of the OSE cell layer in the ovulatory process.…”
Section: Ovarian Surface Epitheliummentioning
confidence: 61%
“…The functional role of P2X7 was investigated in situ by TUNEL assay. P2X7 stimulation with BzATP induced apoptosis in OSE cells and was differential throughout the oestrous cycle; DNA fragmentation was greater during proestrous [70]. These findings contribute to the idea that local factors, such as ATP, may participate in a proposed cyclic proliferation-death equilibrium of the OSE cell layer in the ovulatory process.…”
Section: Ovarian Surface Epitheliummentioning
confidence: 61%
“…The latter process requires cell migration, as indicated by the profile of genes expressed during ovulation, that shows a strong correlation with important epithelial functions, such as the inflammation reaction, angiogenesis, extracellular matrix remodeling and cell-to-cell contact 44 . Both ATP and histamine signaling have been proposed to be involved in ovulation 15 ; in this manner, transmitter-activated membrane ionic currents in the ovarian superficial epithelium might participate during this specific physiological condition, a hypothesis that requires further studies. Nevertheless, an important role for K Ca 3.1 in general epithelial secretory activity is expected, as suggested by its broad expression in most of the epithelial cells analyzed 45 .…”
Section: Discussionmentioning
confidence: 99%
“…SKOV-3 cells are endowed with P2 receptors of the two known subtypes: those forming receptor-channels named P2X 15 , as well as G protein-coupled receptors named P2Y. ATP application generates in SKOV-3 an increase in the intracellular Ca 2+ concentration ([Ca 2+ ] i ) via its release through P2 receptor stimulation 16 , and a similar [Ca 2+ ] i increase is evoked by histaminergic signaling activation; the effect of this [Ca 2+ ] i increase on membrane conductance, however, remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Studies have shown that P2X 7 is expressed in porcine ovarian theca cells and murine/ human ovarian surface epithelium and is involved in ATP-induced apoptotic cell death. [14,27,28] In a previous study, we also reported that P2X 7 was expressed in murine small luteal cells. [14] The activation of P2X 7 receptors decreased the proliferation of luteal cells.…”
Section: Resultsmentioning
confidence: 99%